VITAMIN C: Clay + Ceramic in Contemporary Art. - Morrill, Rebecca; Bier, Arielle; Borthwick, Ben; Bradley, Fiona; Buhe, Elisabeth; Chamberlain, Colby; Ceruti, Mary; Fadda, Reem; Woods, Samantha; Lilley, Clare (London : Phaidon Press, 2017)
Achaintre, Caroline ; Ai Wei Wei ; Amer, Ghada ; Angell, Aaron ; Arancio, Salvatore ; Baga, Trisha ; Baremboym, Alisa ; Benglis, Lynda ; Bhabba, Huma ; Boyle, Shary ; Butterly, Kathy ; Camil, Pia ; Cherubini, Nicole ; Chiandetti, Marco ; Cobbing, William ; Craft, Liz ; Cuddon, Katie ; Cummings, Phoebe ; de Waal, Edmund ; Deacon, Richard ; Merz, Marisa ; Olowska, Paulina ; Ortega, Damien ; Shawky, Wael ; Woodman, Betty
boek